Surface roughness of asteroid (162173) Ryugu and comet 67P/Churyumov–Gerasimenko inferred from in situ observations. Issue 3 (27th October 2020) - Otto, K A; Matz, K-D; Schröder, S E; Parekh, R; Krohn, K; Honda, R; Kameda, S; Jaumann, R; Schmitz, N; Stephan, K; Sugita, S; Tatsumi, E; et al.
ABSTRACT: Alteration processes on asteroid and comet surfaces, such as thermal fracturing, (micrometeorite) impacts or volatile outgassing, are complex mechanisms that form diverse surface morphologies and roughness on various scales. These mechanisms and their interaction may differ on the surfaces of different bodies. Asteroid Ryugu and comet 67P/Churyumov–Gerasimenko, both, have been visited by landers that imaged the surfaces in high spatial resolution. We investigate the surface morphology and roughness of Ryugu and 67P/Churyumov–Gerasimenko based on high-resolution in situ images of 0.2 and 0.8 mm pixel resolution over an approximately 25 and 80 cm wide scene, respectively. To maintain comparability and reproducibility, we introduce a method to extract surface roughness descriptors (fractal dimension, Hurst exponent, joint roughness coefficient, root-mean-square slope, hemispherical crater density, small-scale roughness parameter, and Hapke mean slope angle) from in situ planetary images illuminated by LEDs. We validate our method and choose adequate parameters for an analysis of the roughness of the surfaces. We also derive the roughness descriptors from 3D shape models of Ryugu and orbiter camera images and show that the higher spatially resolved images result in a higher roughness. We find that 67P/Churyumov–Gerasimenko is up to 6 per cent rougher than Ryugu depending on the descriptor used and attribute this difference to the different intrinsic properties of the materials imaged and the erosive processes altering them. On 67P/Churyumov–Gerasimenko sublimation appears to be the main cause for roughness, while on Ryugu micrometeoroid bombardment as well as thermal fatigue and solar weathering may play a significant role in shaping the surface.